2019 16th Canadian Workshop on Information Theory (CWIT) 2019
DOI: 10.1109/cwit.2019.8929920
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Generalized Discrete-Memoryless Push-to-Talk Two-Way Channels

Abstract: In this report, we generalize Shannon's push-to-talk two-way channel (PTT-TWC) by allowing reliable fullduplex transmission as well as noisy reception in the half-duplex (PTT) mode. Viewing a PTT-TWC as two state-dependent one-way channels, we introduce a channel symmetry property pertaining to the one-way channels. Shannon's TWC capacity inner bound is shown to be tight for the generalized model under this symmetry property. We also analytically derive the capacity region, which is shown to be the convex hull… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In [4], Shannon presented a random coding inner bound and a cut-set outer bound to the capacity region. He also exploited channel symmetry properties [4, Section 11] to determine the capacity region in some special cases, which are further generalized in [9]- [14]. For DM-TWCs with symmetry properties, it was shown that Shannon's inner bound is tight, and hence adaptive coding is not needed to achieve capacity.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In [4], Shannon presented a random coding inner bound and a cut-set outer bound to the capacity region. He also exploited channel symmetry properties [4, Section 11] to determine the capacity region in some special cases, which are further generalized in [9]- [14]. For DM-TWCs with symmetry properties, it was shown that Shannon's inner bound is tight, and hence adaptive coding is not needed to achieve capacity.…”
Section: A Literature Reviewmentioning
confidence: 99%